Study of Different Sol-Gel Coatings to Enhance the Lifetime of PDMS Devices: Evaluation of Their Biocompatibility - Aymerich, María (Materials (Basel), 2016)
A study of PDMS (polydimethylsiloxane) sol-gel–coated channels fabricated using soft lithography and a laser direct writing technique is presented. PDMS is a biocompatible material that presents a high versatility to reproduce several structures. It is widely employed in the fabrication of preclinical devices due to its advantages but it presents a rapid chemical deterioration to organic solvents. The use of sol-gel layers to cover the PDMS overcomes this problem since it provides the robustness of glass for the structures made with PDMS, decreasing its deterioration and changing the biocompatibility of the surface. In this work, PDMS channels are coated with three different kinds of sol-gel compositions (60MTES/40TEOS, 70MTES/30TISP and 80MTES/20TISP). The endothelial cell adhesion to the different coated devices is evaluated in order to determine the most suitable sol-gel preparation conditions to enhance cellular adhesion.